(-8y)-11=13

Simple and best practice solution for (-8y)-11=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-8y)-11=13 equation:


Simplifying
(-8y) + -11 = 13

Reorder the terms:
-11 + (-8y) = 13

Solving
-11 + (-8y) = 13

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + (-8y) = 13 + 11

Combine like terms: -11 + 11 = 0
0 + (-8y) = 13 + 11
(-8y) = 13 + 11

Combine like terms: 13 + 11 = 24
(-8y) = 24

Divide each side by '-8'.
y = -3

Simplifying
y = -3

See similar equations:

| 2+8x-7+1-15x-3= | | 15x=(8+7x) | | -12.95-13.9j=17.3-8.4j | | 6z+4=14 | | m+1002= | | 9x+3x-b=3(3x+x) | | 3.77-6.6x+1.11=22.7 | | 24/28 | | 7x-7=-27+5x | | 1/5n-3/10n=1/5 | | y+14/29=-6/29 | | 61.50/1/5 | | 2w-2=11w | | -7.28-4.5n=-13.6n | | 108/243 | | 3z(z+2)=3z*3z+6z-3 | | 12=5-g | | y=7/8(4)+5y | | 7208-220m=320+80m | | 6-6x=5x-9x-6 | | 3(x-1/4)=13/6 | | 6w=50-(1/4)w | | 7+2x=-7x+61 | | 1/2(2x)=5 | | Y/-12-8=4 | | 225/675 | | 5.5?x=?4.5?x | | 1/2d=4 | | -12x+4+8x+x= | | 7.31-6.8+1.11=22.7 | | x-(-2x)= | | 32/184 |

Equations solver categories